PERANCANGAN VISUAL BRAND IDENTITY FESTIVAL IMLEK KOTA TANJUNG PINANG - Mariati Mariati (Universitas Trisakti, 2020)
AbstractDesigning Visual Brand Identity for Tanjung Pinang’s Chinese New Year Festival. Visual brand identity for Tanjung Pinang’s Chinese New Year Festival is one of the efforts to enchance the brand of Riau Islands capital city. Tanjung Pinang city is well known for its historical culture value from Riau Lingga Kingdom so the Malay heritage remains preserved. Chinese New Year festival is the most popular tradition among Chinese people and this year it was held since December 26th 2019 through bazaar untilJanuary 25th 2020 follows by other celebration. This celebration has held a few years ago, but unfortunately not much local tourists known this festival. The purpose of this study is to identify and design a visual brand identity through mascot and logo. The method is descriptive qualitative research based on design. The researcher identified some visual identity consists of style, color, pattern, mascot gesture, 2020 logo and other supporting elements with the concept acculturation of Malay and Chinese culture. AbstrakPerancangan Visual Brand Identity Festival Imlek Kota Tanjung Pinang. Perancangan visual brand identity pada Festival Imlek kota Tanjung Pinang ini merupakan salah satu usaha dalam meningkatkan brand di ibukota provinsi Kepulauan Riau. Kota Tanjung Pinang terkenal dengan budaya nilai histori dari Kerajaan Riau Lingga sehingga ciri khaske-Melayuan-nya tetap dipertahankan. Perayaan Imlek merupakan tradisi paling popular bagi etnis Tionghoa kota Tanjung Pinang dan tahun ini diselenggarakan sejak tanggal 26 Desember 2019 melalui bazar Imlek hingga 25 Januari 2019 untuk pertunjukan lainnya.Perayaan festival Imlek marak diselenggarakan pada beberapa tahun belakangan ini, namun disayangkan belum banyak diketahui oleh turis lokal lainnya. Tujuan penelitian ini yaitu mengidentifikasikan dan merancang identitas visual melalui maskot dan logo untuk perayaan Imlek tahun 2020. Metode yang digunakan adalah penelitian kualitatifdeskriptif yang luarannya berupa perancangan. Identitas visual yang teridentifikasikan berupa style design, warna, pola, gestur maskot, logo 2020, dan elemen pendukung lainnya dengan konsep akulturasi budaya Melayu dan Tionghoa.